Building a story brand : clarify your message so customers will listen - Miller, Donald (Harper Collins Leadership, 2017)
New York Times best-selling author Donald Miller uses the seven universal elements of powerful stories to teach listeners how to dramatically improve how they connect with customers and grow their businesses.
Keywords: Marketing; Brand loyalty